2020
DOI: 10.1016/j.omto.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Replication and Penetration of Oncolytic Adenovirus by Paclitaxel Eradicate Peritoneal Metastasis of Gastric Cancer

Abstract: Peritoneal metastasis is the most frequent form of distant metastasis and recurrence in gastric cancer, and the prognosis is extremely poor due to the resistance of systemic chemotherapy. Here, we demonstrate that intraperitoneal (i.p.) administration of a green fluorescence protein (GFP)-expressing attenuated adenovirus with oncolytic potency (OBP-401) synergistically suppressed the peritoneal metastasis of gastric cancer in combination with paclitaxel (PTX). OBP-401 synergistically suppressed the viability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
(84 reference statements)
0
31
0
Order By: Relevance
“…It was previously reported that hTERT expression is observed in most cancer cells, and almost no hTERT expression is observed in non-cancerous cells (44)(45)(46)(47). Moreover, a telomerase-specific oncolytic adenovirus, OBP-301, was found to considerably reduce tumor weight and increase survival in a nude mouse model of gastric cancer (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that hTERT expression is observed in most cancer cells, and almost no hTERT expression is observed in non-cancerous cells (44)(45)(46)(47). Moreover, a telomerase-specific oncolytic adenovirus, OBP-301, was found to considerably reduce tumor weight and increase survival in a nude mouse model of gastric cancer (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“… 21 Intraperitoneal administration of the oncolytic adenovirus OBP-401 demonstrated significant efficacy in treating peritoneal metastasis in a gastric cancer model. 22 A Phase I trial for the oncolytic vaccinia virus GL-ONC1 in patients with peritoneal carcinomatosis showed tolerability and efficient replication in cancer cells. 23 …”
Section: Introductionmentioning
confidence: 99%
“…administration of OBP-301 synergistically suppressed the peritoneal metastasis of GC in combination with paclitaxel (PTX). 18 In phase I clinical studies, OBP-301 was well tolerated by patients with various cancers. 19 , 20 We have further developed OBP-702 as a modification of OBP-301 that expresses the wild-type p53 gene, so OBP-702 can suppress the viability of various types of tumor cells more efficiently compared with OBP-301 via exogenous p53 overexpression in tumor cells.…”
Section: Introductionmentioning
confidence: 99%